Pemeriksaan Kecacingan Pada Bayi dan Balita Stunting di Desa Wonosalam Kecamatan Wonosalam Kabupaten Jombang - Khanifah, Farach; Sayekti, Sri; Ekowati, Lestari; Kusumawati, Aprilia (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Stunting is a condition of growth failure in children (body and brain growth) due to long-term malnutrition so that children are shorter than normal children of their age and experience delays in thinking. The aim of this activity is to identify the number of children with worms and stunting in Wonosalam Village in collaboration with Posyandu Wonosalam. The targets of this examination are stunted babies and toddlers in Wonosalam Village, Wonosalam District, Jombang Regency. The method used is to provide education about worms and stunting, identify data through distributing worm examination questionnaires. From the results of the examination, 54% of babies and toddlers were identified as suffering from worms because the parents' education level did not understand the dangers of worms and stunting, and the parents' work could also have an influence on the occurrence of stunting. In this identification, 14 respondents were identified as suffering from worms and stunting which resulted in growth and development not being the same as children their age. It is hoped that this activity can contribute to improving the health of babies and toddlers, especially regarding the problem of worm infections. It is also necessary to check babies and toddlers who are not stunted for early detection of worms.